Transparency, Tax Pressure, and Access to Finance - Ellul, Andrew; Jappelli, Tullio; Pagano, Marco; Panunzi, Fausto (Review of Finance, 2016)
Abstract More transparent firms enjoy better access to finance, and also enable closer scrutiny by tax authorities and thus face a heavier tax burden, insofar as they are required to report the same data to tax authorities and investors (book-tax conformity). We study this trade-off in a model with distortionary taxes and finance rationing, and test its predictions on an international dataset. As predicted, firms facing low corporate tax rates choose high transparency, particularly if they are not very dependent on external funding. This result is confirmed by the evidence from statutory tax reforms: reductions of corporate tax rates are followed by increases in firm transparency. Moreover, firms choose higher transparency in countries with high audit quality. Investment is positively correlated with transparency, especially for firms more dependent on external finance. Results are stronger in countries with book-tax conformity.